Documents on the Genocide Convention from the American, British, and Russian archives : the politics of international humanitarian law, 1933-1948 : the ideology of a humanitarian treaty, 1949-1988 : volumes I and II /: the politics of international humanitarian law, 1933-1948 : the ideology of a humanitarian treaty, 1949-1988 : volumes I and II. (2019) - Unknown
No abstract available